2009
DOI: 10.1140/epjb/e2009-00074-x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden critical current drops induced in S/F structures

Abstract: Abstract. In the search for new physical properties of S/F structures, we have found that the superconductor critical current can be controlled by the domain state of the neighboring ferromagnet. The superconductor is a thin wire of thickness ds ≈ 2ξS. Nb/Co and Nb/Py (Permalloy Ni80Fe20) bilayer structures were grown with a significant magnetic anisotropy. Critical current measurements of Nb/Co structures with ferromagnet thickness dF > 30 nm show sudden drops in two very defined steps when the measurements a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 18 publications
6
16
0
Order By: Relevance
“…The thickness transition between these two types is determined by demagnetizing fields which means that it becomes increasingly energetically favourable for domain walls to mutate from out of plane to in-plane direction as films become thinner. This has been shown in experiments in Co, Permalloy (Py) and Ni samples [1,7,[30][31][32] where the transition between these two type of domain walls occurs at around 30 nm for Co and 20 nm for Ni.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…The thickness transition between these two types is determined by demagnetizing fields which means that it becomes increasingly energetically favourable for domain walls to mutate from out of plane to in-plane direction as films become thinner. This has been shown in experiments in Co, Permalloy (Py) and Ni samples [1,7,[30][31][32] where the transition between these two type of domain walls occurs at around 30 nm for Co and 20 nm for Ni.…”
Section: Introductionsupporting
confidence: 52%
“…Our results show sudden drops in the magnetization around coercive fields of the ferromagnet where M ∼ 0 and B ∼ H. This is the response of a normal state material with a weak or no diamagnetic response where the external field can easily penetrate. This results in a reentrant behavior to superconductivity as seen in magnetoresistance measurements in [1]. Similar properties of so called field-induced superconductivity (FIS) have only been realized by magnetic dots array deposited on top of a superconducting Pb film [4].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…As the ferromagnet thickness decreases, demagnetizing fields increase, which means that it becomes increasingly energetically favorable for domain walls to mutate from the out-of-plane to in-plane direction. This has been demonstrated in experiments in Co, Permalloy (Py), and Ni samples, [19][20][21][22] where it has been observed that the transition between these two types of domain walls occurs at around 30 nm for Co and 20 nm for Ni.…”
Section: Introductionmentioning
confidence: 65%